Era Digitalisasi : Keberminatan Profesi Akuntan Publik di Kalangan Mahasiswa Sarjana Akuntansi - Nurhayati, Enung; Rahmawati, Teti; Marliani, Nevi (E-Jurnal Akuntansi, 2023)
The development of digital technology has had an impact on shifting the role of the public accounting profession. However, this is not in line with the unstable growth in the number of public accountants every year. This research aims to analyze accounting students' interest in working as public accountants in the era of digitalization. The population of this research was Accounting students at levels III and IV at private universities in Region III Cirebon, totaling 1,141 students with a total sample of 301 students. The data analysis technique uses Partial Least Square Structural Equation Modeling (PLS-SEM). The research results show that job market considerations, professional recognition, financial rewards and professional training have a significant positive effect, while technological advances in the field of accounting and self-efficacy have no effect on interest in choosing a profession as a public accountant in the era of digitalization. This research can be used as a basis for decision making to increase interest in the public accounting profession in the era of digitalization, especially among accounting students. Keywords: Digitalization Era; Interest; Public Accountant; Profession.